2-NPPA Mitigates Osteoclastogenesis via Reducing TRAF6-Mediated c-fos Expression - Chen, Zhihao; Ding, Mina; Cho, Eunjin; Seong, Jihyoun; Lee, Sunwoo; Lee, Tae-Hoon (Frontiers in Pharmacology, 2021)
Excessive bone resorption leads to bone destruction in pathological bone diseases. Osteoporosis, which occurs when osteoclast-mediated bone resorption exceeds osteoblast-mediated bone synthesis, is regarded a global health challenge. Therefore, it is of great importance to identify agents that can regulate the activity of osteoclasts and prevent bone diseases mediated mainly by bone loss. We screened compounds for this purpose and found that 2-(2-chlorophenoxy)-N-[2-(4-propionyl-1piperazinyl) phenyl] acetamide (2-NPPA) exhibited a strong inhibitory effect on osteoclastogenesis. 2-NPPA suppressed the mRNA and protein expression of several osteoclast-specific markers and blocked the formation of mature osteoclasts, reducing the F-actin ring formation and bone resorption activity. In a cell signaling point of view, 2-NPPA exhibited a significant inhibitory effect on the phosphorylation of nuclear factor kappa-B (NF-κB) and c-fos expression in vitro and prevented ovariectomy-induced bone loss in vivo. These findings highlighted the potential of 2-NPPA as a drug for the treatment of bone loss-mediated disorders.